Effect of charge moistening on alkali roasting of chromium oxide - H. S. Ray; A. K. Tripathy; P. K. Pattnayak (The Institute of Materials, Minerals and Mining, 1905)
The effects of water addition on the solid-state reaction between Cr2O3 and Na2CO3 at low temperatures (up to 873 K) were investigated to determine its possible influence on the reaction rate and the degree of conversion to soluble chromate. Experiments at high temperatures were conducted for comparison. It was found that adding water to the mixture before roasting enhanced both reaction rate and yield significantly. The reactions followed the Lesokhin-Tempelman equation at low temperature and the Ginstling-Brounshtein equation at above 973 K; the respective activation energies were 95 and 22 kJ/mol